A comprehensive review of the latest Indian guidelines on adult immunization - Dhawan, Aditi M.; Desai, Anish; Gvalani, Aanchal; Anand, Sunaina; Das, Priyanka (International Journal Of Community Medicine And Public Health, 2025)
This review consolidates the most recent guidelines on adult immunization issued by the Association of Physicians of India (API) in 2024. The guidelines underscore the importance of immunization in adults, particularly considering the growing geriatric population, projected to make 20% of the population by 2050. Key recommendations include the administration of vaccines for influenza, pneumococcus, hepatitis B and herpes zoster, with specific emphasis on high-risk groups such as healthcare workers, the elderly and individuals with chronic conditions. Additionally, the guidelines highlight the necessity of COVID-19 vaccinations and boosters, considering the emergence of new variants. The API guidelines provide a detailed framework for vaccination schedules, prioritizing clarity and practical implementation for healthcare providers managing patients with multiple co-morbidities. By offering a consolidated and evidence-based approach, these guidelines aim to enhance vaccination coverage and protect against vaccine-preventable diseases in the adult population.